Genetic diversity and demographic history of the Old World Bollworm, Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae), in Ethiopia inferred from mitochondrial gene sequences. Issue 5 (13th May 2022) - Fite, Tarekegn; Tefera, Tadele; Goftishu, Muluken; Damte, Tebekew
Abstract: The Old World bollworm, Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae), is a globally distributed agricultural and horticultural insect pest. Despite the economic importance of this insect in Ethiopia, its genetic diversity and demographic history are poorly understood. We examined the nucleotide variation of the mitochondrial cytochrome c oxidase subunit I (COI) gene fragment of 74 H . armigera individuals from six collection sites in Ethiopia. We recorded 15 COI haplotypes in H . armigera, ten globally shared and five exclusive to Ethiopia (HaET15, HaET14, HaET10, HaET7, and HaET4). Haplotype HaET1 was the most widely geographically distributed and frequent (71.62%). Analysis of molecular variance (AMOVA) revealed a high and significant level of variation within H . armigera populations ( θST  = −0.0135). Negative values of the neutrality test and nonsignificant index of mismatch distribution supported the demographic expansion of H. armigera populations in Ethiopia; furthermore, this was also supported by the nonsignificant values of the sum of squared deviations (SSD) and raggedness index (r). The high genetic variation and population expansion of H . armigera have immense implications for devising locally adapted management strategies in area‐wide integrated pest management IPM programs. However, a comprehensive study of H . armigera genetic diversity and population structure using various molecular markers is needed for future confirmation. Abstract : The TCS of H. armigera haplotypes based on COI gene region showing novel Ethiopian haplotypes (a) and its relation with other countries haplotypes (b)